Battery‐free implantable insulin micropump operating at transcutaneously radio frequency‐transmittable power. Issue 5 (20th December 2019) - Yan, Bingxi; An, Duo; Wang, Xi; DeLong, Brock J.; Kiourti, Asimina; Dungan, Kathleen; Volakis, John L.; Ma, Minglin; Guo, Liang
Abstract: Implantable insulin pumps that can be wirelessly powered may provide a pain‐free solution to continual treatment of Type‐1 diabetes. However, their design and development have long been prohibited by the lack of low‐voltage actuators operated at a wirelessly deliverable small power. Here we introduce a battery‐free insulin pump actuated by a soft and inherently biocompatible polymeric squeezer. At a low voltage below 1.5 V and a small power below 2 mW, which is deliverable using a miniature wireless harvester, our pump consistently delivers a volumetric output of 10 µl within 1 min at a flow rate of 0.21 µl/s. Moreover, comparative studies based on diabetic mice show well agreed blood glucose responses of pump‐ and syringe‐delivery solutions. These encouraging results pave the way for a lightweight, small‐dimension and battery‐free solution to overcome major disadvantages in current implantable insulin pumps.